Achaemenid culture and local traditions in Anatolia, Southern Caucasus and Iran : new discoveries - Ivanchik, A. I. 1965-; Ličʻeli, Vaxtang. (Classical Studies E-Books Online, Collection 2007, ISBN: 9789004222786., 2007)
This book contains papers representing the results of the latest research into the relationship between the 'imperial' culture of the Achaemenids and local traditions. Some of them are devoted to the Southern Caucasus, especially to latest archaeological excavations and to investigations into specific categories of archaeological finds. Other articles concern other regions of the Achaemenid world. The article by L. Summerer represents a publication of a unique work of art: the painting on one of the walls of a wooden tomb in Tatarlı in Western Anatolia, depicting a battle between Persians and warriors of nomadic (Scythian-Saka) appearance. The article by S. Sajjadi presents readers with the results of interesting research, which has been going on in Sistan. Originally published as issue 3-4 of Volume 13 (2007) of Brill's journal Ancient Civilizations from Scythia to Siberia . For more details on this journal, please click here .